PENDIDIKAN DASAR SEBAGAI FONDASI SOSIAL: ANALISIS KOMPARATIF SISTEM PENDIDIKAN INDONESIA DAN KUBA DALAM MEWUJUDKAN PEMERATAAN DAN KUALITAS - Enong Holilah; Ryco Hermawan; Sholeh Hidayat (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study examines the role of basic education as a social pillar in Indonesia and Cuba, two countries that differ significantly in political structures, economic capacity, and public policy orientation. The study aims to describe the efforts of both countries to achieve equitable access to education, improve literacy skills, and fulfill the state’s responsibility in providing quality basic education. In addition, this research identifies strategic lessons that Indonesia can learn from Cuba’s success in strengthening foundational learning. The main argument emphasizes that differences in educational outcomes, particularly in literacy and completion rates, reflect fundamental differences in governance structures, levels of educational investment, and the philosophical foundations of each country’s education system.This study employs a qualitative comparative analysis approach using recent secondary data, including policy documents, scholarly publications, national assessment results, international education indicators from the World Bank for the period 2020–2022, OECD PISA 2022 data, and case studies related to curriculum and literacy programs. The analysis focuses on education governance structures, directions of curriculum reform, literacy improvement strategies, and the distribution and utilization of educational resources. The findings indicate that Cuba has achieved near-universal literacy through centralized governance and sustained national literacy programs, while Indonesia has made progress but continues to face quality disparities due to decentralization challenges and unequal resource distribution.